Differentiation of ICOS+ and ICOS− recent thymic emigrant regulatory T cells (RTE Tregs) during normal pregnancy, pre-eclampsia and HELLP syndrome. (12th October 2015) - Wagner, M I; Jöst, M; Spratte, J; Schaier, M; Mahnke, K; Meuer, S; Zeier, M; Steinborn, A
Summary: Two different subsets of naturally occurring regulatory T cells (nTregs ), defined by their expression of the inducible co-stimulatory (ICOS) molecule, are produced by the human thymus. To examine the differentiation of ICOS + and ICOS − CD45RA + CD31 + recent thymic emigrant (RTE) Tregs during normal pregnancy and in the presence of pre-eclampsia or haemolysis elevated liver enzymes low platelet (HELLP)-syndrome, we used six-colour flow cytometric analysis to determine the changes in the composition of the ICOS + and ICOS − Treg pools with CD45RA + CD31 + RTE Tregs, CD45RA + CD31 − mature naive (MN) Tregs, CD45RA − CD31 + and CD45RA − CD31 − memory Tregs . With the beginning of pregnancy until term, we observed a strong differentiation of both ICOS + and ICOS − CD45RA + CD31 + RTE, but not CD45RA + CD31 − MN Tregs, into CD45RA − CD31 − memory Tregs . At the end of pregnancy, the onset of spontaneous term labour was associated with a significant breakdown of ICOS + CD45RA − CD31 − memory Tregs . However, in the presence of pre-eclampsia, there was a significantly increased differentiation of ICOS + and ICOS − CD45RA + CD31 + RTE Tregs into CD45RA − CD31 + memory Tregs, wherein the lacking differentiation into CD45RA − CD31 − memory Tregs was partially replaced by the increased differentiation of ICOS + and ICOS − CD45RA + CD31 − MN Tregs into CD45RA − CD31 − memory Tregs . In patients with HELLP syndrome, this alternatively increased differentiation of CD45RA − CD31 − MN Tregs seemed to be exaggerated, and presumably restored the suppressive activity of magnetically isolated ICOS + and ICOS − Tregs, which were shown to be significantly less suppressive in pre-eclampsia patients, but not in HELLP syndrome patients. Hence, our findings propose that the regular differentiation of both ICOS + and ICOS − CD45RA + CD31 + RTE Tregs ensures a healthy pregnancy course, while their disturbed differentiation is associated with the occurrence of pre-eclampsia and HELLP syndrome.